THE THE IMPACT OF TEAM WORD WEBBING ON STUDENTS' READING COMPREHENSION AT SMK MA'ARIF NU 01 PURBOLINGGO'S ELEVENTH GRADE - Amirudin Latif; Refa'i M.Pd.; Syaifudin Latif Darmawan; Vina Febriana (Universitas Muhammadiyah Metro, 2022)
The purpose of this study is to determine whether employing the team word-webbing strategy had any appreciable impact on students' reading comprehension of descriptive texts for the eleventh graders at SMK Ma'arif NU 1 Purbolinggo Lampung Timur. In this study, the researcher employed quantitative research using a quasi-experimental approach. Pre-test and post-test were utilized as the tests instruments. Two classes are XI AK 1 and XI AK 2, each class consisted of 40 pupils, served as the sample. The evaluation of the test results places a strong emphasis on the students' ability to comprehend the text. Data analysis utilizing the t-test formula and test analysis using the normality and homogeneity tests are both necessary. Pre-test scores for the experimental group and control group as a whole averaged 64.33 and 65.30, respectively. In contrast, the experimental group's post-test scores were higher than the control group, coming in at 75.80 for the experimental group and 69.80 for the control group. It may be said that using Team Word Webbing in the classroom has a major impact on students' reading comprehension.